Analysis of factors affecting real estate prices in the city of Nur-Sultan - Askarov, A.; Utilov, М.; Zhanuzak, N. (International School of Economics KAZGUU, Nur-Sultan, 2022)
In this study, we analyzed real estate prices over the past decade, and from the econometric analysis, we can see the signs of a bubble in the real estate market in Nur-Sultan. This research starts with a literature review, which discusses bubbles and their life cycles, followed by empirical quantitative methods of analysis. With the data provided, we launched the regression formula and its result. Based on the regression analysis data, we can see that the reduction of the mortgage rate and concessional lending affects the price increase. In this regard, most people have started applying for housing loans to increase their own active funds. During this decade, such programs as "Shanyrak", "Nurly Zher", mortgage lending of "Otbasy Bank" and women's mortgage "Umai" were launched. Сonsequently, the secondary market has increased in prices, although logically it should have fallen over time. Moreover, based on the data obtained, it was noticed that the real incomes of the population have decreased, which suggests that most people are no longer able to pay their mortgage and they have to borrow more money. It was also noticed that nominal income has decreased, which indicates that the majority of the population has stopped earning more compared to previous years. We can justify the increase of prices in the primary real estate market due to the rise in price of construction materials, but we cannot do this for the secondary real estate market. Because of this, we argue that the price increase of real estate is not justified, and this suggests that prices are moving away from the fundamental value, which already indicates a potential bubble in the real estate market.
Keywords: real estate in the city of Nur-Sultan